The Nonmetric Cusp Traits of Maxillary Molars in Tamil Population: A Cross Sectional, Descriptive and Sex Identification study using the Turner Scott dental Anthropology Standards - Jayasankar P. Pillai; Girish Parmar; Jayantkumar M. Vyas; Rajesh Babu (Indian Journal of Dental Research)
Context: Dental nonmetric traits, the morphological characteristics in teeth exhibit variations between populations and sexes. Aim: The aim of the study was to analyse the expression of the cusp traits in maxillary molars in the Tamil Nadu population. Settings and Design: A descriptive, cross-sectional, and population-based study was designed. Methods and Material: The pre-treatment dental models of 236 boys (44.6%) and 293 girls (55.45%) in Tamil Nadu and Pondicherry were used for this study. The expressions of the cusp of Carabelli trait in the maxillary 1st molar and the hypocone trait in the 2nd molar were recorded using the Turner-Scott Dental Anthropology standards. Statistical Analysis Used: The non-parametric Mann–Whitney U test was used to compare the results of males and females. Chi-square test was used to test the inter-trait and intra-trait association. The discriminant function analysis was performed to test the potential of the two traits for sex classification. Results: The prevalence of cusp of Carabelli was only in 7.5%–11.4% of the study sample. The hypocone presence was observed in around 53%–61%. Only 57%–59% of the correct sex classification could be possible using the studied two traits. Conclusions: There was a low prevalence of the maxillary 1st molar Carabelli’s trait in the Tamil population when compared to the prevalence of the distolingual cusp (hypocone) trait in the maxillary 2nd molar. There was an excellent intra-trait correlation while the inter-trait correlation is weak. However, there was a significant association between the two traits on both sides.